2013
DOI: 10.2478/s11686-013-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation in the prevalence of trematodes in the bivalve Perumytilus purpuratus

Abstract: Perumytilus purpuratus is an abundant bivalve located in the intertidal rocky zone of South America that has been considered as a key species of the ecosystem. There are few studies of the host-parasite relationship of this bivalve; thus, this research aims to analyse the spatial and temporal variation in the prevalence of trematodes in P. purpuratus. Bivalves were collected from three localities (El Tabo, Las Cruces and Montemar) of central Chile (33°S, 71°W) during different seasons of 2010. The bivalves wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
0
9
1
2
Order By: Relevance
“…Studies focusing on directly transmission of parasites have also reported a relationship between host abundance and the abundance of digeneans, both influenced by the dry/rainy season cycle (Violante-González et al 2008;Muñoz et al, 2013). Moreover, environmental variations (Violante-González et al 2008;Muñoz et al, 2013), vegetation cover and seasonal variations relating to the dietary behavior of H. malabaricus and H. unitaeniatus may also influence the seasonal infection patterns of metacercariae. These two host fish are piscivorous when adults, while the juvenile fish feeds on plankton, crustaceans, insects and seeds (Santos et al 2006;Soares et al 2011;Alcântara and Tavares-Dias 2015) and mollusks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on directly transmission of parasites have also reported a relationship between host abundance and the abundance of digeneans, both influenced by the dry/rainy season cycle (Violante-González et al 2008;Muñoz et al, 2013). Moreover, environmental variations (Violante-González et al 2008;Muñoz et al, 2013), vegetation cover and seasonal variations relating to the dietary behavior of H. malabaricus and H. unitaeniatus may also influence the seasonal infection patterns of metacercariae. These two host fish are piscivorous when adults, while the juvenile fish feeds on plankton, crustaceans, insects and seeds (Santos et al 2006;Soares et al 2011;Alcântara and Tavares-Dias 2015) and mollusks.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge provides information on different parasite species functions within a community, and also whether these parasitism levels are constant or whether variations are influenced by intermediate host availability. Such variations can alter the recruitment process of parasite species in the environment (Valtonen et 1990;Kadlec et al 2003;Violante-González et al 2008;Neves et al 2013;Soylu 2013;Muñoz et al, 2013;Tavares-Dias et al 2014). Therefore, the effects of seasonality on the parasite infracommunities in wild H. unitaeniatus and H. malabaricus populations in the Amazon region need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…En condiciones cotidianas, éstas se darían a menores latitudes, en verano, y en sitios más altos del intermareal. Al respecto, se ha registrado que esta parasitosis alcanza mayores prevalencias en el nivel medio-alto del intermareal en Chile central (Muñoz et al 2013b). (48, 24, 12, 6, 4, 2 tiempo (1, 2, 4, 6, 12, 24 y 48 h) / Average shedding of cercariae in 14 specimens of P. purpuratus subjected to 2 experiments with opposite cycles of immersion-emersion.…”
Section: Discussionunclassified
“…Odhner, 1911 (Fellodistomidae), y otro digeneo fellodistómido no identificado (Muñoz et al 2013a), y al que diversos autores han denominado Proctoeces lintoni Siddiqi & Cable 1960 (Aldana et al 2009, Oliva et al 2010, aunque aún no ha sido posible determinar taxonómicamente su identidad en forma definitiva (Muñoz et al 2013a, b). Este último taxón es el de mayor prevalencia en P. purpuratus en la costa centro sur de Chile, alcanzando valores menores al 2% (Muñoz et al 2013b), y es el parásito sujeto de este estudio.…”
Section: Introductionunclassified
“…Transmission pathways and factors affecting cercarial dispersion and release have been extensively studied (Curtis 1987;Bao-Zhen et al 1997;McCurdy et al 2000;Miura and Chiba 2007;Thieltges 2007;Fermer et al 2010;BornTorrijos et al 2014a; see Pietrock andMarcogliese 2003 andThieltges et al 2008 for reviews), as well as seasonal and spatial heterogeneity of cercariae (Lang and Dennis 1976;Hughes and Answer 1982;Muñoz et al 2013). However, while detailed descriptions of the parthenogenetic generations inside rediae or sporocysts are available (e.g.…”
Section: Introductionmentioning
confidence: 97%